Strontium-isotope stratigraphy: applications in basin modelling and reservoir correlation - Smalley,PC; Raheim,A; Rundberg,Y; Johansen,H (1989)
The 87Sr/86Sr isotope ratio is homogeneous in sea water at any one time, but has fluctuated during geological time along the path which can be reconstructed by the Sr-isotopic analysis of marine precipitates (eg carbonate or phosphate fossils) of known age. The resultant "seawater curve' can be used as a relative dating tool by analysing carbonate/phosphate fossils from a marine sediment, locating its position on the curve and reading off the corresponding age. Such ages are independent of biofacies or faunal provincialism. A study of Cenozoic sediments from the northern North Sea produced ages on submilligram samples of bioclastic carbonate with precisions of ±0.5-3.0 Ma. When integrated with seismic studies, the results placed important sequence boundaries at approximately 35 Ma, 34-30 Ma and 22 Ma. These boundaries represent hiatuses of various durations. The data illustrate the important potential of Sr-isotope stratigraphy for the production of precise burial histories, which possess the distinct advantage of being based upon dates calculated by an objective numerical method with quantifiable uncertainties. The high quality and resolution of dating and correlation using Sr-isotope stratigraphy, combined with the simplicity and cost-effectiveness of the method, and the increasing availability of access to the analytical instrumentation, suggest that Sr-isotope stratigraphy is set to become a routine technique for basin analysis and correlation in reservoirs. -from Authors